Analysis of the ECB’s monetary management from an endogenous approach - Cárdenas, Luis (Papeles de Europa, 2014)
The aim of this paper is to study monetary policy developed by the European Central Bank (ECB) in recent years, contrasting the monetary effectiveness hypothesis in the case of the Spanish economy. This summarizes the main measures taken during the period, especially during the evolution of the debt crisis, and analyzes the behavior of the main indicators. In contrast to the papers carried out to date, which believe that non-standard monetary policy has met its objectives, in the present study argues that neither benefited nor the Spanish economy has had a expansionary effect on economic activity, i. e., didn’t affect monetary aggregates but the central bank balance sheet. The explanation approach is based on an endogenous money supply and the need for introduction of different monetary policy instruments and social institution reform that monetary policy is effective.